The relationship between Islamic piety (taqwa) and workplace deviance with organizational justice as a moderator - Bhatti, Omar Khalid; Alkahtani, Ali; Hassan, Arif; Sulaiman, Mohamed (Canadian Center of Science and Education, 2015)
Workplace deviance among employees is one of the most prevalent issues faced by today’s organizations globally. Many scholars are keen in studying this phenomenon of workplace deviance because of its high rate of occurrence and severe negative impact on organizations. Research supports the belief that workplace spirituality programs may result in encouraging positive outcomes and can benefit organizations with employees who are more principled, committed, productive, adaptive and innovative. Although, past studies on workplace deviance are well documented, providing an understanding as how situational or individual antecedents may lead to workplace deviance, the problem of workplace deviance remains. Particularly has not been studied from an Islamic perspective. Islam being a comprehensive religion and a complete code of life can provide a suitable solution to manage such an issue. Islamic Piety (Taqwa) is one the most important characteristic of a Muslim. Significantly Islamic spiritual and social responsibility both fall under the purview of Taqwa. An individual holding on to Islamic Piety (Taqwa) can showcase the best of his/her behavior. Therefore the current conceptual study intends to investigate the direct relationships between Taqwa and workplace deviance. In addition this study also proposes to investigate the moderating role of perceived organizational justice (a situational antecedent) between Taqwa and workplace deviance.